State Aid for Newspapers Theories, Cases, Actions - Murschetz, Paul.; Murschetz, Paul. (Media Business and Innovation, 2013)
Ever since newspaper companies first turned to their governments for support in the 1950s, print media has been supported by state aid in many parts of the world. Today, the principles and practicalities of these subsidies have been called into question, endangering the secure funding of expensive high-quality press output. This book provides a comprehensive analysis of today’s global challenges in the print news media’s struggle for survival. It presents current practices concerning government subsidies to newspapers for political, economic, and socio-cultural purposes against the background of declining readership and revenues, increased inter-media competition, austerity budgets imposed on national economies and shifting audience tastes. Using the insights of theoretical debates in the fields of media economics, media governance, and modern management theory, the book analyses these issues by investigating the power of government subsidies to shape and control newspaper markets. It brings together experts in these fields to combine theory with industry practices, aiming to help all parties involved to understand the complexity of issues and requirements necessary to preserve the social benefits of print media.